2001
DOI: 10.1523/jneurosci.21-23-09255.2001
|View full text |Cite
|
Sign up to set email alerts
|

Rabphilin Potentiates SolubleN-Ethylmaleimide Sensitive Factor Attachment Protein Receptor Function Independently of rab3

Abstract: Rabphilin, a putative rab effector, interacts specifically with the GTP-bound form of the synaptic vesicle-associated protein rab3a. In this study, we define in vivo functions for rabphilin through the characterization of mutants that disrupt the Caenorhabditis elegans rabphilin homolog. The mutants do not display the general synaptic defects associated with rab3 lesions, as assayed at the pharmacological, physiological, and ultrastructural level. However, rabphilin mutants exhibit severe lethargy in the absen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 56 publications
3
55
0
1
Order By: Relevance
“…To determine whether RBF-1 is an effector of RAB-27 in vivo, we looked at RBF-1 localization in aex-3 and aex-6 mutant animals. We found that GFP-tagged RBF-1 (RBF-1::GFP) is mislocalized from synapse-rich regions in aex-3(js815) and aex-6(sa24) mutant animals, but RBF-1::GFP is normally localized in rab-3(js49) animals ( Figure 5A; Staunton et al, 2001). We also noted that RBF-1::GFP fluorescence is weaker in aex-6 mutant animals than in wild type.…”
mentioning
confidence: 78%
See 4 more Smart Citations
“…To determine whether RBF-1 is an effector of RAB-27 in vivo, we looked at RBF-1 localization in aex-3 and aex-6 mutant animals. We found that GFP-tagged RBF-1 (RBF-1::GFP) is mislocalized from synapse-rich regions in aex-3(js815) and aex-6(sa24) mutant animals, but RBF-1::GFP is normally localized in rab-3(js49) animals ( Figure 5A; Staunton et al, 2001). We also noted that RBF-1::GFP fluorescence is weaker in aex-6 mutant animals than in wild type.…”
mentioning
confidence: 78%
“…Single mutants rab-3(js49) and rbf-1(js232) Staunton et al, 2001). Double mutants were made by standard crossing procedures jsIs682; jsEx740, jsEx740, jsIs423; jsIs423,.…”
Section: Strains Usedmentioning
confidence: 99%
See 3 more Smart Citations